Sistem Informasi Geografis menggunakan ARCVIEW 3.3 Berbasis Web (Studi Kasus Bidan Praktek Swasta) - Indra Kanedi; Leni Natalia Zulita (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
Along with the continued development of science in computer technology and programming languages today are very helpful advanced world of health, the need to meet the support facilities performance, then one computer in which the current computer technology is not only used by certain circles, the company in business, government, agencies , educational courses and institutions, even individuals to get it, the current high-capacity computer and user interaction manage very difficult especially in the business world managing data.One of the geographical information system using ArcView 3.3 application that is emerging today is an application in the field of Geographic Information System is a computer-based system that is used to store data. Geographic Information Systems to provide data and information in accordance with the geographical location.For Geographical Information Systems Midwives In Bengkulu city is still using a manual system that is recording, came directly to the point of localized to locate Midwife Practices latest must come to the health department, in addition to people who are reluctant to come to the health department will tend to choose to midwives already in the know before.Therefore, researchers and the midwife inted cooperate and agreed to resolve the problem by building a system where by the system using a geographic information system ArcView 3.3 application. Methods that are used in this research is the development of a system where the system is used will be more practical in the information process and the application process is free from error so that the application of Geographic Information Systems midwife in the of Bengkulu city use application ArcView 3.3 can provide geographic information midwife in the bengkulu city of. computerized showing the name of the midwife .Aplikasi Geographic Information System oriented midwife at coordinates X and Y coordinates.